Spatial and morphological effects of tourism urbanisation in the Łódź Metropolitan Area - Makowska-Iskierka, Marzena (Turyzm/Tourism, 2013)
The article presents the effects of urbanisation that took place from 1979 to 2004, on the space of tourism areas in the rural-urban fringe of the Łódź Metropolitan Area. The study concerns morphological changes, i.e. land use, land plot development, as well as the technological and social infrastructure of 24 destinations.